Femtosecond time‐resolved hot carrier energy distributions of photoexcited semiconductor quantum dots. Issue 1 (30th July 2012) - Chuang, Chi‐Hung; Chen, Xiaobo; Burda, Clemens; Hommelhoff, Peter; Kling, Matthias; Stockman, Mark
Abstract Using femtosecond transient absorption spectroscopy, we investigated hot carrier distributions in semiconductor cadmium selenide quantum dots. The relaxation processes represent the behavior of an ensemble of QDs. This concept is applied for analysis with the Fermi‐Dirac distribution and relaxation processes among different electron‐hole pair states. By extracting the experimental hot carrier distribution and fitting with the Fermi‐Dirac function, we resolved the rapid thermalization processes, such as carrier‐carrier and carrier‐phonon interactions was resolved within one picosecond upon photoexcitation. The analysis, using the Fermi‐Dirac distribution modulated by the density of states, provides a general route to understanding the carrier cooling and heat dissipation processes in quantum dot‐based systems.